Women eat more rice and banana: the influence of gender and migration on staple food choice in East Africa - Bechoff, Aurélie; Forsythe, L.; Njau, M.; Martin, A.; Audifas, G.; Abass, A.; Tomlins, Keith I. (Informa UK Limited, 2020)
An original approach was used to examine how staple food choice differs by gender and migration: this consisted of a quantitative survey (six locations with urban consumers from various economic classes (n = 123)), a qualitative in-depth interview with a subset of those consumers (n = 18), and focus group discussions (n = 13). Men and women had similar results in terms of their preferred staple food choice attributes; yet women indicated consuming more rice and banana, and men, more maize and cassava (Chi-squared test; p < .05). Migration status and life stage (formative or adult years) also influenced the type and diversity of staple crops reported.